Penggunaan Bahasa dalam Komunikasi Informasi Publik Pemerintah di Era Digital - Alfianita; Endang Sholihatin (STKIP Subang, 2026)
The importance of language use in delivering public information through government digital media motivates this study. In practice, there are still instances of ineffective language use that may affect public understanding of the information presented. This study aims to analyze the use of language in government social media, news editing, and the management of public information documents (DIP). The research method used is descriptive qualitative, with data collected through observation and documentation of social media captions, news texts before and after editing, and DIP. The results indicate that language used in social media tends to be communicative and concise, while in news and DIP it is more formal and administrative. The news editing process improves clarity and sentence effectiveness. In addition, the presentation of data in the form of bar charts helps simplify information, although clear language use is still required. Overall, the use of language in delivering public information is quite effective, but improvements are still needed in terms of clarity, effectiveness, and consistency of terms.